Utilization of palm oil wastes in the form of palm fiber, palm kernel shell, and palm oil fuel ash as potential aggregates for an interlocking eco-masonry unit - Cahatian, Joseph John O. (2016)
Palm oil wastes are potential aggregates for alternative building materials which are environment-friendly. This study addresses the problem of the applicability and suitability of palm oil wastes in the form of palm oil fibers, palm kernel shells, and palm oil fuel as component aggregates for interlocking eco-masonry unit. The aim is to determine which among the mixture formulations of cement ?limesoil ? palm oil wastes will exhibit the best quality for an eco-masonry unit based on the attributes of appearance, compressive strength, water absorption, flame test, and cost of raw materials. the experiment was limited to seven mixtures. Mixtures 1 to 6 were composed of the different palm oil wastes while Mixture 7 was the control block. It was divided into four major phases: the preparation of raw materials, material development process, product testing and analysis, and identification of uses and applications. The experiment was conducted in a Completely Randomized Design (CRD) with seven mixtures, replicated three times. Data were analyzed using one-way analysis of Variance (ANOVA) and Tukey?s HSD test. The results of the experiment showed that palm oil fuel ash was an ideal aggregate for an eco-masonry unit as it exhibited satisfactory compressive strength and water absorption test results. On the other hand, blocks containing significant amount of palm kernel shell and palm fiber, though exhibiting low water absorption rates, were not suitable for use in construction due to uneven enlargement and deformation during the curing process. For its application, eco-masonry units containing palm oil fuel ash can replace traditional masonry units in interior concrete wall applications. It may also be used in exterior wall applications provided that it will be applied with suitable finishing and waterproofing. For the design project, the primary goal is to utilize the eco-masonry unit in constructing parts of a graduate school building for the University of Southern Mindanao. Using these blocks can lessen cost of construction at the same time create awareness among building users on the importance of using alternative building materials from soil palm waste. This proposed project is designed to meet the demands of a world-class post-graduate education. The project is envisioned to be a model for all subsequent structures in the campus utilizing the palm oil waste based eco-masonry unit while still maintaining an aesthetically pleasing natural and built environment in accordance through green building principles. In addition, un=sing eco-masonry units in public educational institutions can be beneficial because it will show to the public the government ?s support in promoting and helping in raising awareness on the use of sustainable building materials. The spaces needed and required by the graduate school were based and derived from interviews with the graduate school dean as well as the university planning officer. Time-Savers Standards for Building Types, CHED Manual of Regulations for Higher Education, the National Building code, Accessibility law, and Fire Code of the Philippines were used as regulatory basis for space requirements.